IMPLEMENTASI ALGORITMA DIJSKTRA UNTUK PERINGKASAN OTOMATIS ARTIKEL ILMIAH BERBAHASA INGGRIS - Yanuar Budi Prasetyo; Gloria Virginia; Antonius Rachmat Chrismanto (Jurnal Informatika, 2015)
This research implemented Dijkstra algorithm to summarize text documents. To run Dijkstra algorithm, we represented sentence as a vertex and the similarity between sentences as an edge, where the result of the summarization process was the shortest path of Dijkstra calculation. The summarization processes were conducted by utilizing WordNet database and without WordNet database. Our experiment showed that without WordNet the result was better than using WordNet. Using WordNet, the system could obtain 80% relevant sentences. While without WordNet, the system could obtain about 90% of relevant sentences.